Application of Kinematic analysis in rational selection of parameters and operation modes - Vladimir I. Medvedev, Alexander P. Akimov, Yuriy V. Konstantinov,; Ziganshin, Bulat G.; Valiev, Ayrat R.; Mardanov, Ramis Kh.; Galiev, Il’giz G. (Opción, 2019)
The aim of this study is to conduct a kinematic analysis of the BROU to derive the a priori conditions for the rational selection of its design parameters and operation modes via simulation in a mathematical model as methodology. By studying the results of the study we can conclude that the kinematic analysis of the blade rotary operating unit makes it possible to find the cutting angle of a random elementary section of straight and curved cutting edges with regard to the turning angle of the operating unit, its dimensions, and parameters of its operation mode